Tata Letak dan Penerangan Lampu Tenaga Surya pada Akses Jalan menuju Curug Ponggang - SUGIOKO, ANDRE; Hidayat, Trifenaus Prabu; Gunawan, Harjadi; Octaviani, Sandra; Tjahjadi, Fanny (Jurnal Pengabdian Masyarakat Charitas, 2022)
Ponggang Village is located in Serangpanjang District, Subang Regency, West Java. There is a natural beauty in Ponggang Village that is not yet known by many people, namely Curug Ponggang with its natural beauty and soothing atmosphere. To get to Curug Ponggang, there is only one main road access. However, the problem is that there are no lighting facilities on the road access with a road length of 700 meters and a road width of 1.2 meters so that with slippery and steep road access conditions, high vigilance is needed when crossing this road, especially at night or at night. foggy. Therefore, this study aims to examine the planning for the construction of Solar Street Lighting (PJUTS) on the Ponggang Curug access road to improve the comfort and safety of road users. There are 4 alternative concepts, where one selected alternative provides a total PJUTS budget plan for 15 years. The chosen alternative concept uses a PJU lamp post with one arm using a 50W LED Solar Light Model GW8833 lamp. Based on the research that has been done, it takes as many as 22 light points with each lamp post 33 meters apart and the pole height is 3 meters. It is hoped that the construction of these lamps can improve the quality of effective and efficient lighting in Curug Ponggang